Organic Farming as a Model of Sustainable Entrepreneurship - Salar Basiri; Mirmohammad Seyednouri; Ali Farzpourmachiani; Seyedehmona Modaresrad; Mercede Ostadsandiani; Saeid Basiri; Mehdi Farzpourmachiani; Snjezana Baroness Rajacic; Fernando Maldonado Lopes (Pandawa Institute, 2026)
Organic farming is being proposed as one model of sustainable entrepreneurship because it combines environmental benefits, rural livelihoods, and market-based incentives. This review synthesizes the scientific evidence regarding organic agriculture's performance along environmental, economic, and social dimensions and explores how organic systems create both opportunities and constraints for entrepreneurs. I review meta-analytic and review evidence on yields, profitability, ecosystem services, and resilience; discuss practical and structural barriers related to certification, knowledge, scalability, market access, and policy; and outline strategic responses that entrepreneurs and policymakers can use in scaling sustainable agricultural businesses while minimizing trade-offs. The review draws on peer-reviewed meta-analyses and high-quality reviews and concludes with actionable recommendations for entrepreneurs, investors, and policy makers, along with an agenda for future research.